Comparative Study Of AHP And AHP-Topsis In Analyzing Supplier Priority (A Case Study Of Diesel Fuel Supplier At PT. X) - Shelvy Kurniawan; Sambudi Hamali; Sandra Gunawan (Jurnal Manajemen Indonesia, 2020)
The selection of diesel fuel supplier at PT. X which were held in four operational areas, namely South Sumatra, Central Kalimantan, West Kalimantan, and East & North Kalimantan. The purpose is to determine the criterias, subcriterias and their importance weights in the selection of the best diesel fuel suppliers for each operational areas of PT. X. This study will compare the use of two well-known multi-criteria decision making methods namely AHP (Analytical Hierarcy Process) and AHP-TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). The criterias were tested are Quality, Price, Capability, Delivery, Supplier Profile, and Service & Relationship with the results of the highest weighted criteria is Delivery, then followed by the highest weighted subcriteria is Supply Capability. Keywords— AHP, TOPSIS, Supplier Selection, Best Supplier